Association between immunity and viral shedding duration in non-severe SARS-CoV-2 Omicron variant-infected patients - He, Shaojun; Fang, Yanhong; Yang, Jiong; Wang, Wei (Frontiers in Public Health, 2022)
Background Coronavirus disease 2019 (COVID-19) is a respiratory-related disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). More than 200 countries worldwide are affected by this disease. The Omicron variant of SARS-CoV-2 is the major epidemic variant worldwide and is characterized by higher infectivity. However, the immunity and risk factors for prolonged viral elimination in patients with non-severe SARS-CoV-2 Omicron variant infections are unclear. Therefore, this study aimed to examine the relationship between immunity and duration of viral elimination in non-severe SARS-CoV-2 Omicron variant-infected patients in Shanghai. Methods In total, 108 non-severe SARS-CoV-2 Omicron variant-infected patients from Shanghai New International Expo Center Fangcang Shelter Hospital were recruited in this study. They were further allocated to the early elimination (EE) and prolonged elimination (PE) groups according to SARS-CoV-2 nucleic acid positivity duration. Results Compared to patients with EE, those with PE had increased serum concentrations of interleukin (IL)-5, IL-6, and IL-8; higher neutrophil count and neutrophil-to-lymphocyte ratio (NLR); lower lymphocyte, eosinophil, and red blood cell counts; and lower concentrations of hemoglobin and albumin (ALB). In lymphocyte subpopulation analysis, lower numbers of CD3+ T cells, CD4+ T cells, CD8+ T cells, and NK cells and a higher CD4/CD8 ratio were observed in patients with PE. In addition, correlation analysis results revealed that cycle threshold values of SARS-CoV-2 Omicron variant ORF1ab and N were negatively correlated with IL-6 and IL-8 levels and positively correlated with eosinophil count in patients with COVID-19. Finally, multivariate regression analysis showed that ALB, CD4/CD8 ratio, NLR, and eosinophil count were predictors of the SARS-CoV-2 Omicron variant elimination. Conclusion In this study, we identified that the ALB, CD4/CD8 ratio, NLR, and eosinophil count were risk factors for prolonged viral elimination in non-severe SARS-CoV-2 Omicron variant-infected patients. These factors might be efficient indicators in the diagnosis, evaluation, and prognosis monitoring of the disease.